Measuring wine industry efficiency with Wine Industry Network Evaluation Model (WINE-Model) - Mario Arturo Ruiz Estrada; Donghyun Park; Theng Heng Chin (Contemporary Economics, 2020)
We propose a group of indicators for the analysis of wine industry performance. We present a new model that analyzes the direct impact of wine industry productivity rate (Π*), the wine industry performance rate (ΔΠ), the wine cargo expansion rate (ΔΠ), and the wine industry technological change adaptability rate (φ) on wine industry network efficiency (WINE-Index). This new model, "The Wine Industry Network Evaluation Model (WINE-Model)" is intended to offer policy makers and researchers an additional analytical tool to study the impact of dynamic changes such as inter- national trade trends and technological shocks on wine industry performance from a new perspective. The WINE-Model can be applied to the study of any wine industry and is not constrained by geographical area or development stage of the industry. The WINE-Model is thus simple, flexible, and versatile. We apply the model to the wine industries of Spain, Italy, France, Chile, Argentina, and Greece. Perhaps the WINE-Model's biggest strength is its ability to capture and measure industry performance from a dynamic perspective.
Keywords: B41; 330; Wine industry performance; productivity; dynamics; technology; growth